1 м = 100 см; 1 см = 0,01 м 1 дм = 10 см; 1 см = 0,1 дм 2567 см = 2500 см + 60 см + 7 см = 2500*0,01 м + 60*0,1 дм + 7 см = 25 м 6 дм 7 см 2567см+13 м 48 дм 9 см = 25 м 6 дм 7 см + 13 м 48 дм 9 см = (25+13) м + (6+48) дм (7+9) см = 38 м 54 дм 16 см (38 м 54 дм 16 см = 3800 см+540 см+16 см = 4356 см)
13 м 48 дм 9 см = 13*100 см+48*10 см + 9 см= 1300 см+480 см + 9 см = 1789 см 2567см+13 м 48 дм 9 см = 2567 см + 1789 см = 4356 см
4876 кг + 9 т 5 ц 87 кг
1 т = 1000 кг 1 ц = 100 кг 9 т 5 ц 87 кг = 9*1000 кг + 5*100 кг + 87 кг = 9587 кг 4876 кг + 9587 кг =14463 кг
4876 кг = 4000 кг + 800 кг + 76 кг = 4000*0,001 т + 800*0,01 ц + 76 кг = 4 т 8 ц 76 кг 4876 кг + 9 т 5 ц 87 кг = 4 т 8 ц 76 кг + 9 т 5 ц 87 кг = (9+4) т + (8+5) ц + (76+87) кг = 13 т 13 ц 163 кг = 13 т 14 ц 63 гк (163 кг=100 кг + 63 кг = 100*0,01 ц 63 кг = 1 ц 63 кг) (13 т 14 ц 63 кг = 13000 кг + 1400 кг + 63 кг = 14463 кг)
1 м = 100 см; 1 см = 0,01 м 1 дм = 10 см; 1 см = 0,1 дм 2567 см = 2500 см + 60 см + 7 см = 2500*0,01 м + 60*0,1 дм + 7 см = 25 м 6 дм 7 см 2567см+13 м 48 дм 9 см = 25 м 6 дм 7 см + 13 м 48 дм 9 см = (25+13) м + (6+48) дм (7+9) см = 38 м 54 дм 16 см (38 м 54 дм 16 см = 3800 см+540 см+16 см = 4356 см)
13 м 48 дм 9 см = 13*100 см+48*10 см + 9 см= 1300 см+480 см + 9 см = 1789 см 2567см+13 м 48 дм 9 см = 2567 см + 1789 см = 4356 см
4876 кг + 9 т 5 ц 87 кг
1 т = 1000 кг 1 ц = 100 кг 9 т 5 ц 87 кг = 9*1000 кг + 5*100 кг + 87 кг = 9587 кг 4876 кг + 9587 кг =14463 кг
4876 кг = 4000 кг + 800 кг + 76 кг = 4000*0,001 т + 800*0,01 ц + 76 кг = 4 т 8 ц 76 кг 4876 кг + 9 т 5 ц 87 кг = 4 т 8 ц 76 кг + 9 т 5 ц 87 кг = (9+4) т + (8+5) ц + (76+87) кг = 13 т 13 ц 163 кг = 13 т 14 ц 63 гк (163 кг=100 кг + 63 кг = 100*0,01 ц 63 кг = 1 ц 63 кг) (13 т 14 ц 63 кг = 13000 кг + 1400 кг + 63 кг = 14463 кг)
х1 =
; х2 = ![3i](/tpl/images/1282/5956/cd0b2.png)
i - мнимая единица
Пошаговое объяснение:
мнимая единица - величина, квадрат которой равен -1. Обозначается
т.е. ![\sqrt{-1} = i](/tpl/images/1282/5956/ba6ec.png)
х²+9 = 0
x² = -9
x1 =![-\sqrt{-9} = -3\sqrt{-1} =-3i](/tpl/images/1282/5956/9581b.png)
x2 =![\sqrt{-9} = 3\sqrt{-1} =3i](/tpl/images/1282/5956/f1c4b.png)